PELATIHAN BUAT ECOBRICK INDAH (BEBI) DI SEKOLAH DASAR NEGERI CIAWI JATINANGOR - Hasanah, Ferli; Handayani, Vincentia Tri; Wardiani, Sri Rijati (Universitas Padjadjaran, 2025)
Waste is a problem that cannot be avoided in the school environment. Food, paper, plastic, and other types of waste frequently accumulate and are challenging to manage. However, processing plastic waste is the most challenging because it decomposes slowly and requires costly machinery for recycling into new products. Creating eco-bricks is one of the fastest and most cost-effective solutions for managing plastic waste. Ecobricks transform rubbish into a useful resource with significant environmental benefits by compacting clean, dry plastic debris into plastic bottles. This article discusses a community service project that involves ecobrick-making at SDN Ciawi Jatinangor. This activity aims to set an example and raise awareness among elementary school students about the dangers of improper waste disposal, particularly plastic waste, both in school and in drainage systems (watercourses). Through this program, it is expected that Ciawi Elementary School students will be inspired to repurpose their plastic waste rather than disposing of it carelessly. The Service Learning (SL) approach was adopted, involving campaigns and collaboration between teachers and students. Several eco-bricks were made as a direct outcome of this initiative by students using food packaging waste collected from the school environment. The outcomes of this activity were significant, particularly in terms of students’ awareness and behavior. To make this transformation a beneficial habit in society, though, continuous campaigns are still necessary.Sampah merupakan masalah yang tidak bisa dihindari di lingkungan sekolah. Sampah makanan, kertas, plastik dan berbagai jenis sampah lain seringkali menumpuk dan sulit ditanggulangi. Meskipun demikian, sampah plastik merupakan jenis sampah yang paling sulit ditangani karena lama terurai dan jika ingin mengubahnya menjadi produk daur ulang, mesin yang dibutuhkan cukup mahal. Membuat ecobrick adalah cara tercepat dan termurah untuk mengatasi sampah plastik. Ecobrick mengubah sampah menjadi bahan yang berguna dengan cara mengemas sampah plastik yang telah dibersihkan dan dikeringkan di dalam botol. Artikel ini membahas laporan kegiatan Pengabdian Kepada Masyarakat (PKM) tentang pembuatan ecobrick di SDN Ciawi Jatinangor. Tujuan kegiatan ini adalah untuk menggugah kesadaran di antara siswa sekolah akan bahayanya membuang sampah secara sembarangan -khususnya sampah plastik- di sekolah atau bahkan di parit. Dengan kegiatan ini diharapkan siswa SDN Ciawi dapat mengubah sampah plastik yang ada menjadi sesuatu yang berguna. Metode service learning digunakan dalam kegiatan ini dengan kolaborasi siswa dan guru. Beberapa ecobrick berhasil dibuat sebagai hasil langsung dari kegiatan ini. Para siswa menggunakan sampah plastik bekas kemasan makanan yang dikumpulkan sebelumnnya di lingkungan sekolah. Hasil dari kegiatan ini cukup signifikan khususnya dalam pemahaman dan perilaku siswa. Untuk menjadikan transformasi ini sebagai kebiasaan yang bermanfaat di masyarakat, kampanye yang panjang masih perlu dilakukan.